2002
DOI: 10.1177/0145482x0209600607
|View full text |Cite
|
Sign up to set email alerts
|

Reading and Spelling Competence of Dutch Children with Low Vision

Abstract: This comparison of the reading comprehension, decoding, and spelling skills of 404 children with low vision and a norm sample of same-age fully sighted children found that the children with low vision with no additional disabilities performed less well than the sighted children only on decoding, whereas those with additional disabilities performed less well on all the tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 20 publications
2
15
0
1
Order By: Relevance
“…This finding was in keeping with general observations of teachers and existing literature (e.g. Tobin, 1993 in terms of speed; Gompel et al. , 2002 in terms of ‘decoding’).…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding was in keeping with general observations of teachers and existing literature (e.g. Tobin, 1993 in terms of speed; Gompel et al. , 2002 in terms of ‘decoding’).…”
Section: Introductionsupporting
confidence: 91%
“…In line with the discussion presented in the introduction, this is in keeping with the specific findings of Douglas et al (2002), and more general literature (e.g. Tobin, 1993;Gompel et al, 2002).…”
Section: Comparison Of the Ages Of The Two Groupssupporting
confidence: 86%
“…Está ampliamente documentado que los estudiantes con baja visión presentan peores resultados en el reconocimiento de palabras que los alumnos sin dificultades de visión de su misma edad (Corley & Pring, 1993a, 1993bFellenius 1999;van Bon et al, 2000;Gompel et al, 2002;Gompel et al, 2003). La velocidad de un lector con visión normal puede oscilar entre 150 y 400 palabras por minuto, mientras en las personas con discapacidad visual un promedio de unas 90 puede considerarse útil.…”
Section: Antecedentesunclassified
“…The children with low vision were selected from a larger sample of children with low vision who had participated in an earlier study (Gompel et al, 2002). We selected the children on the basis of their visual diagnoses, such that half the children had some form of a visual field restriction and half had intact visual fields.…”
Section: Participantsmentioning
confidence: 99%
“…than do sighted children (Corley & Pring, 1993a, 1993bDaugherty & Moran, 1982;Fellenius, 1999;Gompel, van Bon, Schreuder, & Adriaansen, 2002;Tobin, 1985; van Bon, Adriaansen, Gompel, & Kouwenberg, 2000). A previous study showed that this difference in reading speed should not be attributed to a difference in orthographic knowledge between children with low vision and sighted children (Gompel, Janssen, van Bon, & Schreuder, 2003).…”
mentioning
confidence: 93%